JAEPL, Vol. 4, Winter 1998-1999 (Journal of the Assembly for Expanded Perspectives on Learning, 1998)
Essays Laurence E. Musgrove. Attitudes Toward Writing. This essay describes one teacher's approach to helping students understand the role attitude plays in contributing to or interfering with success in the writing class. Mark McBeth. Body Oddities: Hypothetical (Com)positions from the Physically Extreme. Relying on the anomalous physicalities of the bearded woman, the hermaphrodite, and conjoined twins, this essay explores the links between the body and its constituent performances of composing. Hildy Miller. Goddess Spirituality and Academic Knowledge-Making. Goddess-centered spirituality, an alternative way of making meaning, complements rationalism, the traditional notion of academic knowledge making. Keith Rhodes. Plato, Gorgias, and Trickster: Seeking Rhetoric's Muse. From an historical perspective, rhetoric is the premier Tricksterish art. Seeing this permits us to re-evaluate Plato's role in the history of rhetoric and re-think current practices. Judith Halden-Sullivan. Reflection and an Appetite for Experience: Theory to Classroom Practice. Reflection promotes an openness to thinking and an appetite for experience that must ground everyday classroom practice. Dave Waddell. When a Student Ends a Wounded Silence. Students who disclose psychological trauma may derive therapeutic benefits, and writing teachers should carefully consider their roles. Reviews Katie Kane. Women Writing Culture. (Gary A. Olson and Elizabeth Hirsh, Eds., 1995). Women/ Writing/ Teaching. (Jan Zlotnik Schmidt, Ed., 1998). Sheryl Mylan. ARTiculating: Teaching Writing in a Visual World. (Pamela B. Childers, Eric Hobson, and Joan A. Mullin, 1998). Jerome Bump. Emotional Intelligence. (Daniel Goleman, 1995).